2006
DOI: 10.3138/cmlr.62.3.401
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Motivation to Learn French

Abstract: There is concern among second language educators in Canada that male students are losing interest in studying French as a second language (FSL). In response, in the fall of 2003, a study was conducted to investigate gender differences in second language (L2) motivation among Grade 9 core French students. Building upon the traditional model of L2 motivation that emphasizes learner attitudes toward the target-language community, the researcher broadened the concept of L2 motivation to include both societal and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 17 publications
6
43
3
Order By: Relevance
“…However, few studies investigated gender differences in language learning style of ambiguity tolerance. Among the existing studies this study is in line with Kissau (2006) in his study on 490 French language learners (254 girls, 236 boys) in Ontario who reported no gender difference in tolerance of ambiguity and Saeedeh Karbalaee Kamran (2011). In contract, Sa'dabadi & Sarkhosh (2014) and Maubach & Morgan (2001) revealed that male students had a higher level of ambiguity tolerance compared to their female counterparts.…”
Section: H0 1 : There Is No Significant Relationship Between Universisupporting
confidence: 63%
“…However, few studies investigated gender differences in language learning style of ambiguity tolerance. Among the existing studies this study is in line with Kissau (2006) in his study on 490 French language learners (254 girls, 236 boys) in Ontario who reported no gender difference in tolerance of ambiguity and Saeedeh Karbalaee Kamran (2011). In contract, Sa'dabadi & Sarkhosh (2014) and Maubach & Morgan (2001) revealed that male students had a higher level of ambiguity tolerance compared to their female counterparts.…”
Section: H0 1 : There Is No Significant Relationship Between Universisupporting
confidence: 63%
“…Several studies (Martino, 1999;Whitehead, 1996) have reported on learner preferences for particular subject choice, often revealing a bleak picture for language learning in general and, in particular, for French, which is often judged negatively as a marked language signalling ostentation (Dewaele, 2005) or effeminacy, particularly by boys (Kissau, 2006;Kissau & Wierzalis, 2008). While such studies reveal interesting attitudes to languages, the survey methods and statistical data that are presented often do not extend our understanding of the origins of these attitudes in wider social and economic discourses.…”
Section: Introductionmentioning
confidence: 73%
“…terms used in the revised National Curriculum Programme of Study, 2008, for England and Wales, Qualification and Curriculum Authority [QCA], 2007), popular ideas about the relevance to students' lives inevitably bring to the fore utilitarian perspectives of usefulness, quite apart from the widely held belief that some languages are easier to learn than others. Also, several studies have shown that foreign-language learning is an increasingly gendered area of study and that this is particularly true of French (Kissau, 2006;Kissau & Wierzalis, 2008;Williams, Burden, & Lanvers, 2002). At the same time, the recent removal of compulsion to study foreign languages in the UK after age 14 has laid bare the gulf between the socio-economic groups who invest in language learning (Department for Education and Skills [DfES], 2007).…”
Section: Introductionmentioning
confidence: 96%
“…This reality can be attributed to a number of societal and classroom influences as discussed in the following research. Kissau (2006aKissau ( , 2006bKissau ( , 2007Kissau ( , 2008) published a sequence of research articles from his doctoral research that explored the reasons for gender disparities in FSL programs in Canada. In particular, Kissau (2006a) used a questionnaire and semi-structured interviews with 490 Grade 9 core FSL 1 students to examine student motivation.…”
Section: Enrolment and Attritionmentioning
confidence: 99%